2019
DOI: 10.3390/polym11091505
|View full text |Cite
|
Sign up to set email alerts
|

Simonkolleite Coating on Poly(Amino Acids) to Improve Osteogenesis and Suppress Osteoclast Formation in Vitro

Abstract: Zinc can enhance osteoblastic bone formation and stimulate osteogenic differentiation, suppress the differentiation of osteoclast precursor cells into osteoclasts, and inhibit pathogenic bacterial growth in a dose-dependent manner. In this study, simonkolleite, as a novel zinc resource, was coated on poly (amino acids) (PAA) via suspending PAA powder in different concentrations of zinc chloride (ZnCl2) solution, and the simonkolleite-coated PAA (Zn–PAA) was characterized by SEM, XRD, FT-IR and XPS. Zinc ions w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“… 17 Li et al have shown that the response of BMSCs to zinc coating is highly dose-dependent. 38 The results showed that Zn 2+ released from the Zn2-coated titanium micro-arc oxide coating was not toxic to BMSC proliferation and had good biological safety.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“… 17 Li et al have shown that the response of BMSCs to zinc coating is highly dose-dependent. 38 The results showed that Zn 2+ released from the Zn2-coated titanium micro-arc oxide coating was not toxic to BMSC proliferation and had good biological safety.…”
Section: Resultsmentioning
confidence: 92%
“…Previous studies have shown that BMSCs can survive well under 80 μm concentration of Zn 2+ , higher than this value would be toxic to BMSCs . Li et al have shown that the response of BMSCs to zinc coating is highly dose-dependent . The results showed that Zn 2+ released from the Zn2-coated titanium micro-arc oxide coating was not toxic to BMSC proliferation and had good biological safety.…”
Section: Resultsmentioning
confidence: 98%
“…This also was confirmed by EDS mapping of cycled Zn anodes with/without TPAH, which shows the presence of Zn, O, and Cl (Supplementary Figure S3). It can be noted that simonkolleite, which acts as a corrosion stabilizer, forms in case of high Cl content and low pH value (Yoo et al, 2013;Cousy et al, 2017;Li et al, 2019c). The comparison of Zn electrode surface morphology cycled in beaker cells with and without TPAH addition was done by SEM.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, the poor mechanical properties of pure Zn fail to meet the requirements for orthopedic implants ( Hernández-Escobar et al, 2019 ; Peng et al, 2021b ). Besides, cytotoxicity is prone to be induced due to a high concentration of Zn ions by inhibiting ECM mineralization ( Li et al, 2019a ; Wang et al, 2021b ). Thus, a growing number of studies have focused on alloying Zn-based materials to ameliorate mechanical properties and biocompatibility ( Li et al, 2019b ; Hernández-Escobar et al, 2019 ).…”
Section: Research Progress Of Mg- Zn- and Fe-based Alloy Orthopedic I...mentioning
confidence: 99%